Sheehan’s Syndrome Presenting as Major Depressive Disorder - Mehmood I Qadri (Iranian Journal of Medical Sciences, 2015)
Sheehan’s syndrome or Simmond’s disease is a rare endocrine disorder seen in clinical practice. The clinical spectrum is diverse and a high index of suspicion together with a good clinical acumen and proper diagnostic approach helps in early diagnosis and prompt treatment of this endocrinopathy. Sheehan’s syndrome presenting as a major depressive disorder finds less mention in the literature. The patient discussed here is a 45-year-old female who had been on antidepressants and psychiatry follow up for a long time until she presented to our Out Patient Department (OPD), where she was evaluated in detail and diagnosed as a case of Sheehan’s syndrome. The patient is doing well and is on a regular follow-up with us. Further studies are required to demystify the strength of this association in more detail and to elucidate the possible underlying mechanism.